2017
DOI: 10.1063/1.4987023
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the harmonic oscillator in the space of n-particle Glauber correlators

Abstract: We map the Hilbert space of the quantum Harmonic oscillator to the space of Glauber's nthorder intensity correlators, in effect showing "the correlations between the correlators" for a random sampling of the quantum states. In particular, we show how the popular g (2) function is correlated to the mean population and how a recurrent criterion to identify single-particle states or emitters, namely g (2) < 1/2, actually identifies states with at most two particles on average. Our charting of the Hilbert space al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(151 reference statements)
0
13
0
Order By: Relevance
“…Based on a 2-particle Hilbert space argument, its dip intensity of 58% (i.e. g (2) (0) = 0.42) is consistent with imperfect single photon emission of at most [1-(1-2g (2) ) 1/2 ]/g (2) = 1.42 photons on average 24 . The antibunching lifetime is τ = 132 ps and reflects the tunneling of electrons from Ag(111) to the top C 60 layer.…”
Section: Resultsmentioning
confidence: 64%
“…Based on a 2-particle Hilbert space argument, its dip intensity of 58% (i.e. g (2) (0) = 0.42) is consistent with imperfect single photon emission of at most [1-(1-2g (2) ) 1/2 ]/g (2) = 1.42 photons on average 24 . The antibunching lifetime is τ = 132 ps and reflects the tunneling of electrons from Ag(111) to the top C 60 layer.…”
Section: Resultsmentioning
confidence: 64%
“…These vacuum contributions entered our derivation quite naturally, and its physical origin was only explained afterwards. As indicated by the chosen examples the average photon number is an often determined quantity that may also provide further results on the SP character, compare also [26]. Other figures of merit for SP sources include indistinguishability [33] and coalescence [34] of different SPs, which require more emphasis on the decohering processes and thus the Hamiltonian and dissipative structure of the system at hand.…”
Section: Discussionmentioning
confidence: 97%
“…[28,29]. At this point, it is worth comparing with the results from [26]. In that work it was shown that g (2) 1/2 implies that the average photon number á ñ n has to be smaller or equal to 2, the equality given for the Fock state and thus  -[ ( )] q n n 2 1 n .…”
Section: Different Interpretations Based On˜( ) Gmentioning
confidence: 97%
See 2 more Smart Citations